Program Activities of Mareka Community Reading Garden in Fostering Community Interest in Reading in Mendatte Village - Elihami Elihami; Aminullah Aminullah; Lilis Angreny (LP2M Universitas Muhammadiyah Enrekang, 2022)
The community service activity is an effort to assist the Mareka Reading Park in Enrekang Regency. It is worthy of fostering the spirit of reading in Fostering Community Interest in Reading in Mendatte Village. Taman Baca Mareka benefits from improving the quality of human resources in realizing a reading culture society and fostering interest, love, and passion for reading